Spontaneous subconjunctival abscess in congenital lamellar ichthyosis - Shivanand C Bubanale; Linda Maria Genoveva De Piedade Sequeira; Bhagyajyothi B Kurbet (Indian Journal of Ophthalmology, 2018)
Congenital lamellar ichthyosis is an autosomal recessive, heterogeneous disorder presenting at birth with generalized skin involvement. The most common ophthalmic manifestation noted is bilateral ectropion of the lower eyelids. A 1-month-old female neonate, the second born of a nonconsanguineous marriage, presented with 4 days' history of redness, discharge, and swelling in the right eye. There was severe right upper eyelid ectropion, conjunctival injection, chemosis, a subconjunctival mass on the temporal bulbar conjunctiva spontaneously draining pus and corneal haze. The anterior chamber, iris, lens and fundus appeared normal. Congenital lamellar ichthyosis was suspected because of scaling and excessive dryness of the entire body. The occurrence of a spontaneous subconjunctival abscess is not known in lamellar ichthyosis. We thus report the management of a rare case of unilateral upper eyelid ectropion, subconjunctival abscess with orbital cellulitis in congenital lamellar ichthyosis.